IMPLEMENTATION OF AN INTEGRATED DISCOVERY LEARNING MODEL FOR GENERIC SCIENCE SKILLS ON ACID - BASE MATERIAL - Rambe, Anisa Putri (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
Abstract: This research aims to determine the effect of Prior Knowledge Evaluation (EPA) and the influence of Student Worksheets (LKPD) on Learning Outcomes Evaluation (EHB) and to determine the differences in learning outcomes between students who have high initial knowledge and students who have low initial knowledge by using Discovery Learning (DL) model integrated Generic Science Skills (KGS) in Acid Base material. This research was carried out using a dual paradigm design with two independent variables (X), namely the EPA value and LKPD value and one dependent variable (Y), namely the EHB value. The population in this study were all class XI MIPA 2 of SMA S IT PMDU Kisaran and the sample for this research was class Implementation of the learning model is carried out using learning tools in the form of teaching materials and LKPD. The instruments used in taking student grades consist of EPA questions, LKPD, EHB and student observation sheets during learning. Data analysis used multiple linear regression tests and independent sample t-tests. The test results show that there is a significant influence between the EPA and LKPD values on the EHB value. There are also differences in EHB scores between students with high initial abilities and students with low initial abilities. Keywords: Discovery Learning, KGS, Acids and Bases. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh Evaluasi Pengetahuan Awal (EPA) dan pengaruh Lembar Kerja Peserta Didik (LKPD) terhadap Evaluasi Hasil Belajar (EHB) dan untuk mengetahui perbedaan hasil belajar antara peserta didik yang memiliki pengetahuan awal tinggi dan peserta didik yang memiliki pengetahuan awal rendah dengan menggunakan model Discovery Learning (DL) terintegrasi Keterampilan Generik Sains (KGS) pada materi Asam Basa. Penelitian ini dilaksanakan menggunakan desain paradigma ganda dengan dua variabel bebas (X) yaitu nilai EPA dan nilai LKPD dan satu variabel terikat (Y) yaitu nilai EHB. Populasi dalam penelitian ini adalah seluruh peserta didik kelas XI SMA S IT PMDU Kisaran dan sampel dalam penelitian ini kelas XI MIPA 2 sebanyak 32 orang peserta didik yang dipilih dengan teknik purposive sampling. Implementasi model pembelajaran dilakukan dengan menggunakan perangkat pembelajaran berupa bahan ajar dan LKPD. Adapun instrumen yang digunakan dalam pengambilan nilai peserta didik yang terdiri dari soal EPA, LKPD, EHB dan lembar observasi peserta didik selama pembelajaran. Analisis data menggunakan uji regresi linear ganda dan uji independent sample t-Test. Hasil uji menunjukkan bahwa terdapat pengaruh yang signifikan antara nilai EPA dan LKPD terhadap nilai EHB. Terdapat pula perbedaan nilai EHB antara peserta didik dengan kemampuan awal tinggi dan peserta didik dengan kemampuan awal rendah. Kata Kunci: Discovery Learning, KGS, Asam dan Basa.